Construction of A Recombinant Virus Between Poliovirus and Coxsackie A Virus 11 - Utama, Andi; Shimizu, Hiroyuki (BRIN, 2005)
Recent outbreaks of circulating vaccine-derived poliovirus (cVDPV) revealed the possibility of recombination between vaccine strains poliovirus (PV) and cluster C enterovirus. Based on genetic analysis, it is assumed that coxsackie A virus 11 (CAV-11), one f the cluster C enterovirus, may naturally recombine with PV. To elucidate this hypothesis, the chimeric virus between PJ156, a type I cVDPV isolate isolated from an acute flaccid paralysis (AFP) case in the Philippines in 2001, and CAV-11 (PJ156/CAV-11) was constructed by using long-PCR method. As the result , PJ156/CAV-11 was viable in HEp-2 cell line. The PJ156/CAV-11 exhibited mostly similar phenotype with parental PJ156 in term of plaque size, viral growth and neuroviruJence. These results suggested that recombination between PV and CAV-11 might naturally occur during transmission of vaccine strains in the community. The effect of recombination on the viral phenotype is significantly depending on the counterpart virus.